2023
DOI: 10.3390/atmos14040712
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Current Primary Measures to Mitigate Brake Wear Particle Emissions from Light-Duty Vehicles

Abstract: Exhaust regulations and improved exhaust gas treatment systems have already initiated the trend that brings emissions from brakes and tires to the forefront of traffic-induced particulate matter. The health and environmental relevance of particulate matter has resulted in regulators, industry, and research institutions prioritising the mitigation of non-exhaust particle emissions. To this end, under the umbrella of the United Nations Economic Commission for Europe World Forum for Harmonisation of Vehicle Regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 35 publications
8
22
0
Order By: Relevance
“…0.107) based on actual vehicles. These results indicate the need for vehicle-specific friction brake share coefficients, a conclusion consistent with a previous study [17]. Using electrified vehicle brakes as FFBs and a single coefficient for each group does not allow for fair brake-wear particle measurements, especially fair PN measurements.…”
Section: Pm10 Pm25 and Tpnsupporting
confidence: 75%
See 1 more Smart Citation
“…0.107) based on actual vehicles. These results indicate the need for vehicle-specific friction brake share coefficients, a conclusion consistent with a previous study [17]. Using electrified vehicle brakes as FFBs and a single coefficient for each group does not allow for fair brake-wear particle measurements, especially fair PN measurements.…”
Section: Pm10 Pm25 and Tpnsupporting
confidence: 75%
“…Friction brakes that share coefficients that depend on the electric vehicle type have been implemented in this method to allow third-party laboratories to perform tests based on the GTR24 procedure. Although this friction brake share coefficient was the first step of the study of brake wear particle emissions for vehicle with regenerative brake systems, the method does not represent actual regenerative braking characteristics and needs to be improved [17]. Based on environmental policy making processes in Japan [18], the Automotive Emissions Expert Committee of Japan has been discussing this issue and is in the process of developing the Future Measures to Reduce Automobile Emissions (Fifteenth Report).…”
Section: Introductionmentioning
confidence: 99%
“…Mass loss as a wear factor was 9.31 mg/km per brake with ECE pads (Figure 1). A comparison of these results to the benchmarks of a previous interlaboratory study (ILS) [8] revealed that higher emissions were observed in that study than in this study (6.5 mg/km per brake with NAO pads and 21 mg/km per brake with ECE pads) [26,27]. NAO was developed to optimize comfort (reduction of noise and rim contamination), and this study (Figure 1) as well as previous studies have shown higher emissions with ECE than with NAO [26].…”
Section: Brake Pad and Disc Wearsupporting
confidence: 47%
“…Similarly, Storch et al 21 reported that wear particles from drum brakes initially accumulated in the drum but began escaping from the drum once saturation of the accumulation was reached. This resulted in a steady state level of emissions after an initial phase.…”
Section: Discussionmentioning
confidence: 93%